OPTICAL FIBERS AND THEIR APPLICATION IN COMMUNICATIONS - Rafal Adnan Hasan (Western European Studies, 2025)
Fiber optic technology is a modern and innovative method used to transmit data across different geographical regions. It offers several advantages, including high speed, long transmission distances, and excellent signal quality. Numerous studies and practical applications have proven that using fiber optics provides high quality and is the optimal choice both technically and economically. Fiber optics have many benefits, such as low signal loss and lightweight construction, but the most important feature is their extremely high bandwidth capacity, reaching thousands of billions of bits per second. This has made them a prominent solution in the field of telecommunications, replacing copper wires in a variety of applications, including long-distance lines, underwater cables, and telephone exchange connections.
Keywords: fiber; communications; geography